2009
DOI: 10.1097/jsm.0b013e318190ba06
|View full text |Cite
|
Sign up to set email alerts
|

Differential Emotional Responses of Varsity Athletes to Concussion and Musculoskeletal Injuries

Abstract: The results revealed that both injured groups experienced emotional disturbance after injury. More importantly, the findings strongly suggest that the emotional reaction after concussion is different from that of musculoskeletal injury. Therefore, we concluded that assessing emotional reactions to concussion is particularly important and recommend that sports medicine professionals assess and monitor emotional functioning as well as somatic complaints and neurocognitive changes during recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 27 publications
4
78
2
Order By: Relevance
“…Our findings support previous research in which patients who sustained anterior cruciate ligament injuries had elevated postinjury depressive scores for a longer duration than did concussed patients. 12 However, our results contrast with those of Hutchison et al, 11 who demonstrated that athletes who sustained minor musculoskeletal injuries experienced 2-week postinjury depressive symptoms that were not different from preinjury levels. Both groups used the Profile of Mood States short version, a scale consisting of 7 subscales: Tension, Depression, Anger, Vigor, Fatigue, Confusion, and Self-Esteem.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our findings support previous research in which patients who sustained anterior cruciate ligament injuries had elevated postinjury depressive scores for a longer duration than did concussed patients. 12 However, our results contrast with those of Hutchison et al, 11 who demonstrated that athletes who sustained minor musculoskeletal injuries experienced 2-week postinjury depressive symptoms that were not different from preinjury levels. Both groups used the Profile of Mood States short version, a scale consisting of 7 subscales: Tension, Depression, Anger, Vigor, Fatigue, Confusion, and Self-Esteem.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, no significant differences in baseline CES-D scores were evident among the concussed, injured/nonconcussed, and healthy control groups. These findings support previous work [10][11][12] that suggested emotional dysfunction before injury was not the cause of the postinjury changes in depressive symptoms reported by the concussed and injured/nonconcussed groups.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations